Using attendance data in non-medical health interventions: A case study of Cape Town NPOs - Kettlewell, Finlay (Department of Sociology, 2024)
Within health promotion NPOs, the effective collection, collation and analysis of attendance data can be hugely beneficial to a wide variety of organisational processes. These include the interlinked processes of monitoring, evaluation and impact assessment, as well as broader organisational streamlining, fundraising and safeguarding among others. Despite the various uses that attendance data can serve, many NPOs in the Cape Town area have been failing to either collect it accurately, collate it effectively and efficiently, or to analyse and utilise it in a manner which benefits the organisation. This research project, in the form of a multi-case case study design, sought to investigate the barriers faced by Cape Town NPOs to the effective collection, collation and utilisation of beneficiary attendance data. The study used semi-structured interviews, and respondents included staff from 4 organisations of varying financial means and socio-economic positionalities. Within each organisation, respondents included fieldworkers, Monitoring and Evaluation managers, and upper management in order to gain a wide range of perspectives across the attendance data flow. Among the findings of this research project, the following factors were reported as being the most significant barriers to the effective collection, collation and utilisation of attendance data: Firstly, respondents reported a lack of funder-borne motivation to collect attendance data at a useful level. This combined with a second factor, a lack of time and human capacity within organisations to engage in activities outside of immediate funding briefs, to push attendance data collection off organisational priority lists. Thirdly, a majority of staff at less-resourced organisations, as well as fieldworkers at wellresourced organisations, did not demonstrate a good understanding of attendance data's different forms or uses. Finally, digital tools which could be used to ameliorate attendance data-related struggles were often prohibitively complicated or expensive for use in the South African context. This research strongly recommends the revisiting of attendance data's importance by funders, and that those funders provide NPOs with adequate training and tools so that the potentially immense benefits of good quality attendance data are not wasted.